A Brief Political Economy of Energy Subsidies in the Middle East and North Africa - Laura El-Katiri; Bassam Fattouh (Revue Internationale de Politique de Développement, 2017)
Energy subsidies are among the most pervasive and controversial fiscal policy tools used in the Middle East and North Africa (MENA). In a region with few functioning social welfare systems, subsidised energy prices continue to form an important social safety net, albeit a highly costly and inefficient one. In the MENA region’s oil and gas producing countries, low energy prices have also historically formed an important element of an unwritten social contract, where governments have extracted their countries’ hydrocarbon riches in return for citizens’ participation in sharing resource rents. While it is clear that energy subsidy reform will not be the only variable at play, its potential socio-economic dividends are important factors for enabling some common regional objectives—sustainable fiscal policies, fiscal space to invest in key areas, and a more efficient and equitable distribution of scarce resources—to be achieved, helping to promote a more stable political status quo in the long term. If accommodated by effective mitigation measures, reforming energy subsidies in the MENA region’s middle-income economies could be a powerful tool for governments—addressing those very profound socio-economic grievances that have contributed to the outbreak of political protest and, in some cases, to an intensification of domestic infighting over political control. In this paper, we look at some of the MENA region’s potential avenues for reform. While the past has demonstrated the political difficulty of reforming energy prices, recent experience also shows that the reform of energy subsidies can be achieved, if accompanied by a set of enabling factors.